A two-step optimization strategy for 2nd generation ethanol production using softwood hemicellulosic hydrolysate as fermentation substrate. (November 2017) - Boboescu, Iulian-Zoltan; Gélinas, Malorie; Beigbeder, Jean-Baptiste; Lavoie, Jean-Michel
Highlights: 8 factors concerning yeast, nutrients and process parameters were investigated. Yeast inoculum, pH and nutrient availability were determined the most significant. Process modeling was performed and optimization scenarios were predicted. A maximum of 74.27% of hemicellulosic ethanol yield was produced. Optimization confirmations and bioreactor scale-up were performed. Abstract: Ethanol production using waste biomass represents a very attractive approach. However, there are considerable challenges preventing a wide distribution of these novel technologies. Thus, a fractional-factorial screening of process variables and Saccharomyces cerevisiae yeast inoculum conditions was performed using a synthetic fermentation media. Subsequently, a response-surface methodology was developed for maximizing ethanol yields using a hemicellulosic solution generated through the chemical hydrolysis of steam treatment broth obtained from residual softwood biomass. In addition, nutrient supplementation using starch-based ethanol production by-products was investigated. An ethanol yield of 74.27% of the theoretical maximum was observed for an initial concentration of 65.17 g/L total monomeric sugars. The two-step experimental strategy used in this work represents the first successful attempt to developed and use a model to make predictions regarding the optimal ethanol production using both softwood feedstock residues as well as 1st generation ethanol production by-products.